Parent Progeny Regression Analysis for Yield and Yield Contributing Traits in F3 and F4 Generations in Rice (Oryza sativa L.) - Blessy, V.; Murugan, E.; Suresh, R.; Gnanamalar, R. P.; Kumar, S. Vellai; Kanchana, S. (International Journal of Bio-resource and Stress Management, 2022)
The present study was carried out during kharif (June−September, 2019) and from January to mid of May 2020 at AC&RI, Madurai, Tamilnadu state, India. From the segregating populations of F3 and F4 generations of the cross ASD16×Improved Pusa Basmati 1 to estimate the effectiveness of selection for yield and its contributing traits. F3 generation was raised in single seed decent method in the non-replicated manner and line sowing was taken in F4 generation. Positively skewed and platykurtic curve was observed for the trait hundred seed weight in the both generations this result revealed that the trait was controlled by the complementary type of gene action hence showing that intense selection is needed to obtain more genetic gain from these traits. The parent progeny regression and intergenerational correlation showed positive and highly significance for the quantitative traits i.e., days to 50% flowering, number of productive tillers, number of filled grains panicle-1, and single plant yield, plant height and hundred grain weight. Narrow sense heritability was observed for the traits viz., days to 50% flowering, single plant yield, number of productive tillers, panicle length, number of filled grains panicle-1 infer that these traits carried their additive×additive component and helped in the fixation of the characters in the early generation itself.